Renal denervation in secondary arterial hypertension therapy: clinical case - A. Yu. Orekhov; L. K. Karazhanova; A. A. Chinibaeva; A. B. Zhaksebergenova (Российский кардиологический журнал, 2024)
Introduction. Renovascular hypertension is one of the most severe types of hypertension in terms of the choice of treatment strategy. Recent studies have not provided a clear answer to the question of which treatment approach (conservative or surgical) is most appropriate for these patients.Brief description. The presented case describes a female patient with a longterm uncontrolled hypertension, whose examination revealed bilateral renal artery stenosis. Considering the debatable clinical effectiveness of revascularization of renal artery stenosis, the patient underwent distal renal artery denervation using multielectrode catheters. A decrease in blood pressure was shown. Follow-up of the patient demonstrated stable antihypertensive effect of the procedure, as well as its safety in case of impaired renal function.Discussion. This clinical demonstrates the third way in the treatment of patients with renal arteries stenosis and resistant hypertension — renal sympathetic denervation. This method requires a separate controlled study with individuals with renal dysfunction, including renovascular origin.